Is Enneagram Personality System Able to Predict Perceived Risk of Heart Disease and Readiness to Lifestyle Modification? - Komasi, Saeid (Ann Card Anaesth, 2019)
BACKGROUND: Studying personality traits and patterns is of significant importance in adopting healthy behaviors. Therefore, the current study investigates the relationship between Enneagram personality types and perceived risk of heart disease and readiness to lifestyle modification. METHODS: In this cross-sectional study, 190 noncardiac patients (82.3% female) in an outpatient clinic in western Iran were selected using a simple random sampling method to fill out standard questionnaires. The obtained data were analyzed using Pearson's correlation coefficient and linear regression analysis. RESULTS: The findings show that the performer personality (Type 3) can directly predict increasing readiness to lifestyle modification (P < 0.001). In contrast, there is a reverse significant relationship between the challenger personality (Type 8) and readiness to lifestyle modification (P = 0.019). Moreover, the helper personality (Type 6) is able to directly predict increasing the perceived risk of heart disease (P = 0.012). CONCLUSIONS: In the Enneagram system, unique personality types possess a unique risk perception and readiness to adopt healthy behaviors. The results of the current study can provide valuable information for healthy lifestyle programs professionals with regard to preventing cardiovascular diseases.